Thematic structure of research on crop weeds in Poland - Jackowiak, Bogdan (Biodiversity: Research and Conservation, 2017)
The paper presents an analysis of problems of arable field weeds discussed by Polish authors in 2853 botanical scientific works published in the years 1870-2015. The research included both widely available publications and scientific works that appeared in Polish in regional and local journals, as well as the brief conference proceeding. The thematic structure of Polish studies on segetal weeds consists of several levels and includes eight main thematic groups and 51 subgroups. The review and multi-subject works were included in the ninth group. Taking into account the number of publications, main thematic groups are ranked as follows: (1) Weed flora and vegetation: structure, distribution and dynamics; (2) Weediness of different crop types, crop fields and fallow lands; (3) Interactions between weeds and the environment; (4) Biology and weed development; (5) Variability, taxonomy and weed diagnostics; (6) Research methodology; (7) Extinction and protection of weeds; (8) Weeds of archaeological localities.